2018
DOI: 10.1073/pnas.1806851116
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin signaling via MICAL3 induces symmetric cell division to expand breast cancer stem-like cells

Abstract: SignificanceTumors are composed of both cancer stem-like cells (CSCs) and differentiated cancer cells. Each CSC can undergo either a symmetric cell division to produce two CSCs or an asymmetric cell division to produce one CSC and one differentiated cancer cell. It is believed that the rate of symmetric division increases as more CSCs become malignant; however, underlying molecular mechanisms remain elusive. Here we show that stimulation with a cytokine, semaphorin (Sema), activates monooxygenase of MICAL3, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 38 publications
4
35
0
Order By: Relevance
“…Previous work from our group and others has shown that ACD is not the dominant mode of cell division used by CSCs during tumor growth (Lathia et al, 2011;Xin et al, 2012). These findings have also been confirmed using mathematical modelling to suggest an evolutionary disadvantage for ACD (Daynac et al, 2018;Guichet et al, 2016;Mukherjee et al, 2016;Obernier et al, 2018;Sugiarto et al, 2011;Tomasetti and Levy, 2010;Tominaga et al, 2019). However, these assessments have not been done in the context of the selective pressures induced by therapies.…”
Section: Discussion Of Key Findingssupporting
confidence: 60%
“…Previous work from our group and others has shown that ACD is not the dominant mode of cell division used by CSCs during tumor growth (Lathia et al, 2011;Xin et al, 2012). These findings have also been confirmed using mathematical modelling to suggest an evolutionary disadvantage for ACD (Daynac et al, 2018;Guichet et al, 2016;Mukherjee et al, 2016;Obernier et al, 2018;Sugiarto et al, 2011;Tomasetti and Levy, 2010;Tominaga et al, 2019). However, these assessments have not been done in the context of the selective pressures induced by therapies.…”
Section: Discussion Of Key Findingssupporting
confidence: 60%
“…Recently, we have reported that semaphorin signaling via MICAL3/collapsin response mediator protein 2 (CRMP2)/Numb axis contributes to the maintenance of breast CSCs by inducing symmetric cell division [105] . .…”
Section: Treatment Approaches Targeting Other Activated Signaling Patmentioning
confidence: 99%
“…Researchers believe that as CSCs become more malignant, they become more likely to divide symmetrically. Since SCD produces both two daughter CSCs, SCD leads to effectively the expansion of the CSC population (33,(45)(46)(47)(48). The concept of ACD therapy, which suppresses CSCs symmetrical division and inhibits CSCs expansion, may establish a new strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%